2005
DOI: 10.1093/humupd/dmi006
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and ageing

Abstract: The late 20th century trend to delay birth of the first child until the age at which female fecundity or reproductive capacity is lower has increased the incidence of age-related infertility. The trend and its consequences have also stimulated interest in the possible factors in the female and the male that may contribute to the decline in fecundity with age; in the means that exist to predict fecundity; and in the consequences for pregnancy and childbirth. In the female, the number of oocytes decreases with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
141
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 507 publications
(150 citation statements)
references
References 93 publications
3
141
0
6
Order By: Relevance
“…[3,17,20,24] However, despite significant medical advances in technology, ARTs cannot fully compensate for age-related fertility decline. [27,28] Given the relatively low success rates of IVF for women in their late 30s and early 40s, and estimated success rates of between 2% and 12% using cryopreserved eggs [29] these advanced reproductive technologies may be giving women of AMA false hope about their ability to safely delay childbearing. [10][11][12][13] Some have suggested that, in relying on ARTs to extend the reproductive lifespan, women may indeed be "sleepwalking into infertility".…”
Section: Literature Reviewmentioning
confidence: 99%
“…[3,17,20,24] However, despite significant medical advances in technology, ARTs cannot fully compensate for age-related fertility decline. [27,28] Given the relatively low success rates of IVF for women in their late 30s and early 40s, and estimated success rates of between 2% and 12% using cryopreserved eggs [29] these advanced reproductive technologies may be giving women of AMA false hope about their ability to safely delay childbearing. [10][11][12][13] Some have suggested that, in relying on ARTs to extend the reproductive lifespan, women may indeed be "sleepwalking into infertility".…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study revealed that the oocyte retrieval rate declines significantly with age. There is an evident gradual decline in female fecundity with age, particularly noticeable in those who are older than 30 years, accelerating between the ages of 35 and 40, and reducing to almost zero by 45 years 4, 5. There is also a decrease in the ovarian reserve with age, caused by the decreased number of oocytes and the concomitant increase in the rate of oocyte aneuploidy and subsequent reduced reproductive potential 6.…”
Section: Discussionmentioning
confidence: 99%
“…However, endometrial degeneration is probably not the primary contributor to the age-related decline in mare fertility. Embryos flushed from the oviducts of mares $20 years of age have been reported to undergo delayed cleavage and to contain fewer cells than those from younger mares (Carnevale and Ginther 1995), analogous to the situation in older compared with younger women (Baird et al 2005). Combined with studies demonstrating that embryos from mares .18 years show lower survival rates than embryos from mares ,6 years after transfer to young recipients (Ball et al 1989), this indicates that the loss of developmental potential is intrinsic to the ovulated oocyte or arises during very early (intra-oviductal) embryo development.…”
Section: Introductionmentioning
confidence: 92%